Analisis Perlindungan Hukum Atas Merek Terdaftar Sebagai Hak Atas Kekayaan Intelektual (Studi pada Kantor Wilayah Kementerian Hukum dan HAM Provinsi Lampung) - Herlina Ratna SN (KEADILAN PROGRESIF, 2016)
Protection of Intellectual Property Rights (IPR) is a step forward for the nation of Indonesia who in 2020 entered the era of the free market. One of the intellectual property rights which requires a person to register are trademarks. The problem in this research is how the legal effect of the mark registered as intellectual property rights? The method used is a normative juridical approach, the source of the data obtained from the library. Secondary data types Data collected by literature study further in qualitative analysis. The results showed the legal effect on the Registrant's brand as an intellectual property rights owner Getting rights to the brand, gain the protection of a registered trademark infringement and filed both civil and criminal. Suggested to the Directorate General of Intellectual Property Rights Regional Office of the Ministry of Justice and Human Rights Lampung to disseminate the importance of trademark registration for legal protection to trademark holders.